During wind and rain : the Jones family farm in the Arkansas Delta, 1848-2006 - Bolsterli, Margaret Jones (University of Arkansas Press, 2008)
Margaret Jones Bolsterli is the author of Born in the Delta and the editor of Vinegar Pie and Chicken Bread and A Remembrance of Eden. She is a professor emerita of English at the University of Arkansas, Fayetteville.